Application of conformal mapping to the determination of unsteady temperature distribution in thermally orthotropic plates. - Laura, P. A. A.; Gutiérrez, G. H.; Sánchez Sarmiento, G. (North Holland Publishing Co., 1979)
Fil: Laura, P. A. A. Comisión Nacional de Energía Atómica; Argentina